THE ROLE OF ISLAMIC FINANCING IN SUPPORTING STATE FINANCE THROUGH COMMUNITY DRIVEN DEVELOPMENT SCHEME - Pratama, Raditya Hendra; Adi Wibowo, Wisnu Cahya (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2025)
Sharia-compliant financing instruments need to be given a broader scope to support the State Budget (APBN). This research aims to find the potential of intensifying the role of the waqf financing scheme in the state budget financing using the Community Driven Development (CDD) scheme by maximizing the role of social control. This study was carried out using a qualitative approach with triangulation, combining a literature review and interviews with key informants to examine the opportunities for Islamic finance to contribute to State Budget (APBN) financing by utilizing aspects of the Fogg Behavior Model in the behavior of Indonesian Muslims. The results of this research provide conclusions and recommendations that waqf has great potential to contribute to state budget financing with the use of the CDD design that can be utilized by the government, financial institutions, and the Islamic finance industry to optimize the role of Sharia-compliant financing in supporting the State Budget (APBN).